2018
DOI: 10.1155/2018/1417528
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogasteras a Model for Diabetes Type 2 Progression

Abstract: Drosophila melanogaster has been used as a very versatile and potent model in the past few years for studies in metabolism and metabolic disorders, including diabetes types 1 and 2. Drosophila insulin signaling, despite having seven insulin-like peptides with partially redundant functions, is very similar to the human insulin pathway and has served to study many different aspects of diabetes and the diabetic state. Yet, very few studies have addressed the chronic nature of diabetes, key for understanding the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 229 publications
(251 reference statements)
0
56
0
2
Order By: Relevance
“…Both chemicals are toxic analogues of glucose transported to cells via Glut 2 transporter. Both treatments lead to insulin-producing cells necrosis, but by different mechanisms (Álvarez-Rendón et al, 2018).…”
Section: Chemically Inducedmentioning
confidence: 99%
See 2 more Smart Citations
“…Both chemicals are toxic analogues of glucose transported to cells via Glut 2 transporter. Both treatments lead to insulin-producing cells necrosis, but by different mechanisms (Álvarez-Rendón et al, 2018).…”
Section: Chemically Inducedmentioning
confidence: 99%
“…Scientific literature on alloxane as a diabetogenic agent is extensively revised (Carvalho et al, 2003). The site of its diabetogenic action is the beta cell of the pancreas, the binding of this substance being very fast, generating toxic free radicals, leading to cell death by necrosis (Álvarez-Rendón et al, 2018;Rohilla & Ali, 2012). STZ is synthesized by the yeast Streptomycetes achromogenes and was initially identified as antimicrobial, however, preclinical studies revealed that its administration in high doses caused the destruction of β-pancreatic cells (Delfino et al, 2002;Furman, 2015).…”
Section: Chemically Inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a growing number of genes and particular alleles that affect the proclivity to develop diabetes mellitus type II in humans [6], clouding results undertaken using human subjects with varying genetic backgrounds, making comparisons between studies difficult. The same is true of most diabetic animal models where genetic homogeneity is not strictly enforced [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial characterization of the first viable mutant in the Drosophila insulin pathway more than twenty years ago [9], the fruit fly has become a favored organism for insulin studies [7]. The insulin pathway in flies is evolutionarily conserved and has been extensively characterized [7, 10].…”
Section: Introductionmentioning
confidence: 99%